The Impact of Surgical Patent Ductus Arteriosus Closure on Autonomic Function in Premature Infants - Andescavage, Nickie N.; Metzler, Marina; Govindan, Vedavalli; Al-Shargabi, Tareq; Nath, Dilip S.; Krishnan, Anita; Massaro, An; Wang, Yunfei; duPlessis, Adre J.; Govindan, R. B. (American Journal of Perinatology, 2017)
Background Patent ductus arteriosus (PDA) is a common complication of prematurity and a risk factor for poor outcome. Infants undergoing surgical PDA ligation are at highest risk for neurodevelopmental injury. Autonomic dysfunction has been described in premature infants with PDA.Aim To interrogate the autonomic nervous system by analysis of advanced heart rate variability (HRV) metrics before and after surgical closure of the PDA.Study Design Prospective, observational study.Subjects Twenty-seven infants born before 28 weeks' gestation were included in this study.Methods Continuous electrocardiogram data were sampled at a rate of 125 Hz for a total of 6 hours before and 6 hours after 30 hours of surgical closure. HRV was determined by detrended fluctuation analysis to calculate the short and long root mean square (RMSL and RMSS) and α components at two time scales (long and short).Results Gestational age (GA) was positively associated with RMSL, RMSS, and αS and was negatively associated with αL. There was no difference between RMSs, RMSL, αS, or αL before and after surgery; however, median heart rate was lower after surgery (p < 0.01).Conclusion Advancing GA is highly associated with increasing HRV; however, surgical ligation does not affect HRV in the postoperative period.
Keywords: heart rate variability; patent ductus arteriosus; surgical closure; premature infants